Microscopic lattice method for studying intracellular reaction-diffusion kinetics / Chew Wei Xiang - Chew , Wei Xiang (2019)
Reaction and diffusion plays fundamental roles in many intracellular biochemical process. Bottom-up modelling approaches provide a way to connect the microscopic reactiondiffusion influenced by intracellular conditions to the macroscopic cellular behavior. However, microscopic computational method that diffuses the molecule in the continuum, such as the Brownian dynamics simulation, require long duration to simulate reactiondiffusion up to the subcellular scale. In contrast, simulation scheme based on microscopic lattice method (MLM) that represent each molecule explicitly as a random walker on lattice voxels has a relatively low computational cost. Yet, the theory and consistency of MLM have not been clarified in detail. In this work, we performed in-depth analysis on MLM based on the Spatiocyte simulation scheme in solving diffusion-influenced reaction. We construct the theoretical framework for MLM based on the Smoluchowski-Collins-Kimball model for bimolecular reaction and the random walk theory. By matching the MLM theory with the continuum-based theory, we obtain the expressions for determining the simulation parameter. The MLM theory and the simulation result is then validated with the continuum-based theory and simulation method. We also show that the run time of MLM is an order of magnitude faster than continuum-based method for simulating macromolecules diffusion at typical intracellular concentrations. We have performed several case studies on reaction-diffusion process often encountered in the cell. Finally, we discuss the applicability and limitation of MLM.